Long-Circulating and Fusogenic Liposomes Loaded with Paclitaxel and Doxorubicin: Effect of Excipient, Freezing, and Freeze-Drying on Quality Attributes - Marjorie Roque; Danilo Geraldes; Caroline da Silva; Mônica Oliveira; Laura Nascimento (MDPI AG, 2022)
Liposomes can increase plasma half-life, enhance targeting, and diminish the side-effects of loaded drugs. On the downside, physical and chemical instabilities of dispersions often result in a reduced lifespan, which limits their availability on the market. Solid formulations obtained by freeze-drying can immobilize vesicles and provide extended shelf life. For both processes, the choice of excipients and process parameters are crucial to protect the carrier layers against tension caused by freezing and/or dehydration. The aim of this work is to evaluate the influence of freezing and drying parameters, besides excipient choice, to obtain solid long-circulating and fusogenic liposomes (LCFL-PTX/DXR) co-encapsulating paclitaxel (PTX) and doxorubicin (DXR) at a synergistic ratio (1:10). Methods: LCFL-PTX/DXR was evaluated by freeze-drying microscopy (glass transition, Tg'), differential scanning calorimetry (collapse temperature, Tc), freeze-thawing and freeze-drying processes. Freeze-dried samples were evaluated by thermogravimetry (residual moisture) and the resuspended liposomes were characterized in terms of size, polydispersity index (PI), zeta potential (ZP), and drug content. Liposomes morphology was evaluated by cryomicroscopy. Results: Trehalose protected PTX cargo upon freeze-thawing and more than 80% of the original DXR retention. The formulations with trehalose resulted in a cake with 5-7% of moisture content (200-240 nm); 44-60% of PTX retention, and 25-35% of DXR retention, with the variations caused by cryoprotector concentration and process changes. Conclusions: Trehalose protected liposome integrity, maintaining PTX retention and most of DXR upon freeze-thawing. Freeze-drying reduced the retention of both drugs inside all liposomes, whereas formulation with trehalose presented minor losses. Therefore, this frozen formulation is an alternative product option, with no need for manipulation before use.